Function analysis of GhWRKY53 regulating cotton resistance to verticillium wilt by JA and SA signaling pathways - Li, Youzhong; Chen, Haihong; Wang, Youwu; Zhu, Jincheng; Zhang, Xiaoli; Sun, Jie; Liu, Feng; Zhao, Yiying (Frontiers in Plant Science, 2023)
WRKY transcription factors (TFs) play an important role in regulating the mechanism of plant self-defense. However, the function of most WRKY TFs in upland cotton (Gossypium hirsutum) is still unknown. Hence, studying the molecular mechanism of WRKY TFs in the resistance of cotton to Verticillium dahliae is of great significance to enhancing cotton disease resistance and improving its fiber quality. In this study, Bioinformatics has been used to characterize the cotton WRKY53 gene family. we analyzed the GhWRKY53 expression patterns in different resistant upland cotton cultivars treated with salicylic acid (SA) and methyl jasmonate (MeJA). Additionally, GhWRKY53 was silenced using a virus-induced gene silencing (VIGS) to determine the contribution of GhWRKY53 to V. dahliae resistance in cotton. The result showed that GhWRKY53 mediated SA and MeJA signal transduction pathways. After VIGS of the GhWRKY53, the ability of cotton to resist V. dahliae decreased, indicating that the GhWRKY53 could be involved in the disease resistance mechanism of cotton. Studies on the levels of SA and jasmonic acid (JA) and their related pathway genes demonstrated that the silencing of GhWRKY53 inhibited the SA pathway and activated the JA pathway, thereby reducing the resistance of plants to V. dahliae. In conclusion, GhWRKY53 could change the tolerance of upland cotton to V. dahliae by regulating the expression of SA and JA pathway-related genes. However, the interaction mechanism between JA and SA signaling pathways in cotton in response to V. dahliae requires further study.